MODALITY MODALITY OF INTERPERSONAL MEANING IN BACHARUDDIN JUSUF HABIBIE’S SPEECH - Diana Sopha (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2023)
Focus of this research is to analyze Modality in interpersonal meaning of Systemic Functional Language. This research objective is to find out how Modality is used in Bacharuddin Jusuf Habibie’s speech. Modality is analyzed in BJ Habibie’s speech by using qualitative method. Various types of Modality is used in his speech including Modalization and Modulation explicitly and implicitly. The two types of Modalization are used in his speech namely Probability and Usuality. The two types of Modulation are also expressed in his speech namely Obligation and Inclination. The degree used is also varied from high, middle and low degree. Another type of Modality used is Appearance in high and low degree.